Fracture Behaviors of Miniature Size Specimens of Sn-5Sb Lead-Free Solder under Tensile and Fatigue Conditions. (2017) - Kobayashi, Kyosuke; Shohji, Ikuo; Koyama, Shinji; Hokazono, Hiroaki
Abstract: Tensile and low cycle fatigue properties of Sn-5Sb (mass%) solder were investigated with miniature size tensile specimens. The effects of temperature and strain rate on tensile properties and the effect of temperature on low cycle fatigue properties were examined. Moreover, fracture behaviors of the specimens were investigated. Tensile strength and 0.1% proof stress increased with increasing strain rate and decreased with increasing temperature. The effects of temperature and strain rate on elongation were negligible. Chisel point fracture was observed in all specimens after the tensile test. The low cycle fatigue life of Sn-5Sb obeyed the Manson-Coffin's equation and fatigue ductility exponent, α was approximately 0.6 in the temperature range from 25 o C to 150 o C. From the observation for fracture surfaces and side areas of the fractured parts, it was found that cracking such as phase boundary cracking is dominant under fatigue conditions in the miniature size Sn-5Sb alloy.